Negotiation of the Religious Identity among Youth from Mixed Interreligious Immigrant Muslim Families in Spain: Gender Dynamics, Possibilities and Constraints - Ortiz, Anna; Rodríguez-García, Dan; Solana-Solana, Miguel (Migraciones. Publicación del Instituto Universitario de Estudios sobre Migraciones, 2021)
Spain has experienced in recent decades a significant increase in the mixed unions between natives and immigrants with one of the spouses being Muslim. In this article we present the results of a pioneering and exploratory study on the negotiation of the religious identity of youth descendants of these interreligious couples, in a context of prevalent secularism and islamophobia. Drawing on the analysis of interviews, the results show that these young people negotiate their cultural-religious belonging in a myriad of ways, with positive or negative experiences depending on various factors, mainly gender. In this sense, the study of cultural-religious mixedness can enlighten us in a double sense: on the one hand, to emphasise the socially transformative value of mixed/multiple cultural backgrounds, and, on the other hand, to highlighting the persistence of divisions that limit social inclusion and social cohesion.